Penyuluhan Hukum Mengenai Bullying Sebagai Bentuk Upaya Preventif Terhadap Perilaku Bullying Pada Remaja - Faisal, Fitriah; Zuliarti, Wa Ode; Handrawan, Handrawan; Tarta, Ahmad Firman; Widyastuti, Endah; Saputra, Idris (Universitas Halu Oleo, 2024)
This community service is based on the prevalence of bullying behaviour among teenagers, especially in the school environment, which can come from peers, seniors and even other parties in the school environment, such as teachers. Lack of understanding regarding what constitutes bullying, lack of understanding regarding the effects and legal consequences of bullying. Relevant parties make policies regarding bullying in the school environment. The aim of this community service activity is to increase understanding of the law through legal counseling regarding bullying as a form of preventive effort against bullying behaviour in teenagers. . This activity was carried out at SMAN 1 Kendari as one of the favorite schools in Kendari City, Southeast Sulawesi Province. Legal counseling is carried out by means of question-and-answer discussions. The results achieved in this community service activity are that participants in community service activities are able to understand and know about what is categorized as bullying behaviour, how to prevent and report this behaviour. This can be seen from the enthusiasm of the students or activity participants which is characterized by positive responses and actively asking questions and answers to the presenters regarding bullying and prevention efforts as well as parties who can be involved in the problem solving process.